DETERMINAN TAX AVOIDANCE STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN PERIODE 2019-2021 - Siti Sundari; Cahyani Nuswandari (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
Tax avoidance is an act of tax avoidance that is carried out legally or in other words does not violate the applicable tax laws in Indonesia, namely by exploiting the weaknesses of these regulations or with certain schemes. This study aim to re-examine several variiables the influence tax avoidance, namely variables of profitabilty, leverage company size, audit committee and executive charater in mining sector companies listed on the stock exchange in 2019-2021. Determination of the sample of this study using purposive sampling method. The research data analysis method uses multiple regression analysis. The results showed that leverage, company size, audit committee and executive character had no effect on tax avoidance while profitability had a significant positive effect on tax avoidance.